The effect of working environment on job satisfaction among public sectors employees: a case of Johor Tenggara Board of Development (KEJORA) / Nurul Amira Raihana Roslan - Roslan, Nurul Amira Raihana (Faculty of Business and Management, 2018)
The issue of employee satisfaction has been notable in recent times in order to make sure the development of the employees and accomplishment of an organization itself. So, the aim of this research is to investigate the effect of working environment towards job satisfaction on public sector employees in Johor Tenggara Board of Development (KEJORA). Specifically, this research looks to investigate the working environment may affect job satisfaction, which are to establish the extent to which working hours influences job satisfaction of employees in public sectors, to determine the influence of top management on job satisfaction of employees in public sectors, to exhibit the extent to which job security influence job satisfaction of employees in public sectors, to establish the influence of relationship with co-workers towards job satisfaction of employees in public sectors, and lastly to determine the extent to which salary influences job satisfaction of employees in public sectors. All of the data used to conduct this research will be collected through questionnaires and also will adopt descriptive statistics analytical techniques to examine all of the variables using Statistical Program for Social Sciences (SPSS). Lastly, the findings will be reported in the form of tables and figures and appropriate recommendations given.